2010
DOI: 10.1038/aps.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pressor response to acute Ang II infusion in mice lacking membrane-associated prostaglandin E2 synthase-1

Abstract: Aim: To examine the contribution of vascular membrane-associated prostaglandin E2 synthase-1 (mPGES-1) to acute blood pressure homeostasis. Methods: Angiotensin II (AngII, 75 pmol·kg -1 ·min -1 ) was continuously infused via the jugular vein into wild-type and mPGES-1 -/-mice for 30 min, and blood pressure was measured by carotid arterial catheterization. RT-PCR and immunohistochemistry were performed to detect the expression and localization of mPGES-1 in the mouse arterial vessels. Mesenteric arteries were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…51 Among multiple enzymes involved in PGE 2 production, COX-1 and mPGES-1 are constitutively expressed in vascular tissues and cultured VSMCs. 16 In the present study, after arterial injury of mice, the expression of COX-2 but not COX-1 was transiently upregulated for less than 1 week. However, the mPGES-1 expression was constantly elevated for at least 4 weeks.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…51 Among multiple enzymes involved in PGE 2 production, COX-1 and mPGES-1 are constitutively expressed in vascular tissues and cultured VSMCs. 16 In the present study, after arterial injury of mice, the expression of COX-2 but not COX-1 was transiently upregulated for less than 1 week. However, the mPGES-1 expression was constantly elevated for at least 4 weeks.…”
Section: Discussionsupporting
confidence: 43%
“…12,13 PGE 2 production is increased in atherosclerotic lesions of both laboratory animals and humans. 14,15 COX-1 and microsomal PGE 2 synthase-1 (mPGES-1) are expressed in normal vessels, 16 whereas COX-2 and mPGES-1 expression is induced in wire-injured 17 and balloon-injured 18 vessels. These observations suggest that PGE 2 may have an important role in vascular remodeling after angioplasty.…”
mentioning
confidence: 99%
“…Zhang et al further confirmed the vasodilatory and antihypertensive role of mPGES-1 during acute ANG II infusion. (75) Salazar FJ et al employed a selective mPGES-1 inhibitor (PF-458) to study the renal effects of prolonged mPGES-1 inhibition. (76) The results showed mPGES-1 inhibition reduced renal blood flow (RBF) in dogs with low salt intake (LSI), but did not alter glomerular filtration rate (GFR) or renal hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II induced hypertension was also uninfluenced by mPGES-1 deletion in hyperlipidemic mice [11, 21]. These results are somewhat inconsistent with the findings from Jia et al and Zhang et al who did note that mPGES-1 deletion augmented the hypertensive response to both salt loading and angiotensin II infusion [22, 23]. Interestingly, using Cre-LoxP mediated cell specific gene depletion, our own data illustrated that neither myeloid nor vascular cell mPGES-1 play a major role in blood pressure homeostasis, at least at baseline and hyperlipidemia conditions [14].…”
Section: Mpges-1 and Blood Pressurementioning
confidence: 96%